PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA - Rizky Pratama Linnes (Departemen Matematika, 2018)
One of the abilitiy that must be mastered by students in learning mathematics is understanding of mathematical concepts. In fact, students’ understanding of mathematical concepts is still low. The solution to solve this problem is by applying cooperative learning model Numbered Heads Together (NHT) type. The purpose of this study is to view whether students’ understanding of mathematical concepts who learning by using cooperative learning model NHT type is better than conventional learning. This study is quasi experiment with static group design. Sampling is done by simple random sampling. The results shows that students’ understanding of mathematical concepts who learning by using cooperative learning model NHT type is better than conventional learning. Keywords – conventional learning, numbered heads together, understanding of mathematical concepts